Implementation of Customer Relationship Management (CRM) to Improve Customer Retention (A Case Study of Supermarkets in the Kelapa Gading Area of North Jakarta) - Esa Aulia; Afina Putri Vindiana (Devotion : Journal of Research and Community Service, 2026)
This research was motivated by the intense competition within the modern retail industry in the digital economy era, which has encouraged companies to shift from transactional strategies toward relationship marketing approaches to maintain business sustainability. The premium supermarket sector in North Jakarta faces significant challenges in retaining customers with high expectations amid increasingly aggressive competitor promotions. This study aimed to describe the implementation of Customer Relationship Management (CRM) and evaluate its effectiveness, measured through the dimensions of People, Process, Product, and Information Technology (IT), both partially and simultaneously in relation to customer retention among supermarkets in the Kelapa Gading area, North Jakarta. This study employed a quantitative descriptive and verification approach, with primary data collected through questionnaires distributed to 102 respondents selected using a purposive sampling technique. Data were analyzed using Multiple Linear Regression Analysis with the assistance of SPSS software. The results of the partial hypothesis testing (t-test) showed that the People, Product, and IT dimensions had positive and significant effects on customer retention, with the People dimension being the most dominant factor. In contrast, the Process dimension did not have a significant effect on customer retention, indicating that operational processes were perceived as a basic standard rather than a differentiating factor among premium consumers. Simultaneously, the F-test results demonstrated that all CRM dimensions significantly affected customer retention, with an explanatory contribution of 43.6% based on the Adjusted R-squared value, while the remaining 56.4% was influenced by other external factors not examined in this study.